2011
DOI: 10.1177/8756479311424433
|View full text |Cite
|
Sign up to set email alerts
|

Amyand Hernia Diagnosed With Sonography

Abstract: Individually, inguinal hernias and acute appendicitis are common, but the combination of the two, acute appendicitis within an inguinal hernia or Amyand hernia (AH), is rare. The overwhelming majority of AH cases are in males and discovered during surgery. To date, only three case reports in the literature of this pathology have been diagnosed with sonography. This is a report of an AH diagnosed in a woman with sonography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
(25 reference statements)
0
3
0
2
Order By: Relevance
“…It typically presents on the right side based on the anatomy, but it has also been presented on the left due to gut malrotation, situs inversus totalis, and a very mobile cecum [3]. Because patients may present with nonspecific symptoms, this remains a difficult diagnosis to make preoperatively and hence is mainly found intraoperatively during surgical exploration of a complicated inguinal hernia [4]. A classification system designed to diagnose and treat Amyand's hernia was created and is called the Losanoff and Basson's criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It typically presents on the right side based on the anatomy, but it has also been presented on the left due to gut malrotation, situs inversus totalis, and a very mobile cecum [3]. Because patients may present with nonspecific symptoms, this remains a difficult diagnosis to make preoperatively and hence is mainly found intraoperatively during surgical exploration of a complicated inguinal hernia [4]. A classification system designed to diagnose and treat Amyand's hernia was created and is called the Losanoff and Basson's criteria.…”
Section: Discussionmentioning
confidence: 99%
“…With ultrasound playing a large role in diagnosis as well, you may see non-compressible, dilated, blind-ending bowel loops with a luminal diameter of more than 7.2 cm within the inguinal canal with or without inflammation [3]. Ultrasound may have additional benefits of being real-time and visualize certain features unavailable with the CT scan [4]. Recent cases have demonstrated that laparoscopy is becoming the leading choice for treatment based on staging of the hernia and inflammation of the appendix due to improvements in preoperative diagnosis with CT and ultrasound [5].…”
Section: Discussionmentioning
confidence: 99%
“…CT remains the imaging modality of choice for patients with groin mass. However, there are several cases in the literature where the Amyand hernia was diagnosed via ultrasound examination [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…El hallazgo del apéndice vermiforme dentro de una hernia inguinal se conoce como hernia de Amyand (HA) 1 . La coexistencia de una apendicitis aguda dentro de un saco herniario es rara 2 . Claudius Amyand fue el primero en describir su incisión en un niño de 11 años que presentaba un absceso inguinal; durante la cirugía encontró el apéndice dentro de un saco herniario.…”
Section: Introductionunclassified
“…Claudius Amyand fue el primero en describir su incisión en un niño de 11 años que presentaba un absceso inguinal; durante la cirugía encontró el apéndice dentro de un saco herniario. El paciente se recuperó tras la escisión apendicular y la reparación de la hernia 2 . La incidencia de HA es de aproximadamente un 1% y se complica con apendicitis aguda en el 0,08% de los casos 3 .…”
Section: Introductionunclassified